2021
DOI: 10.1111/ner.13237
|View full text |Cite
|
Sign up to set email alerts
|

Asleep Surgery May Improve the Therapeutic Window for Deep Brain Stimulation of the Subthalamic Nucleus

Abstract: Objective The effect of anesthesia type in terms of asleep vs. awake deep brain stimulation (DBS) surgery on therapeutic window (TW) has not been investigated so far. The objective of the study was to investigate whether asleep DBS surgery of the subthalamic nucleus (STN) improves TW for both directional (dDBS) and omnidirectional (oDBS) stimulation in a large single‐center population. Materials and Methods A total of 104 consecutive patients with Parkinson's disease (PD) undergoing STN‐DBS surgery (80 asleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…No anesthesia-related clinical issues were noted, and clinical outcomes in the asleep group were equivalent or better than those of the awake group. Recently, we could also show that our modified anesthesia protocol may increase therapeutic window compared to conventional awake surgery [ 31 ]. Together, this supports the safety and effectiveness of this approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No anesthesia-related clinical issues were noted, and clinical outcomes in the asleep group were equivalent or better than those of the awake group. Recently, we could also show that our modified anesthesia protocol may increase therapeutic window compared to conventional awake surgery [ 31 ]. Together, this supports the safety and effectiveness of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Taking another approach, DBS implantations can also be completed in asleep patients, that is, under full general anesthesia. Clinical outcomes of awake and asleep lead placements have generally been equivalent [7,8,16,31,34,37], albeit with small sample sizes and high patient heterogeneity in some comparative trials. The equivalence of asleep procedures, together with the face validity of increased patient comfort, has led to a shifting of perspectives that makes asleep DBS procedures the preferred approach [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senemmar et al reported that asleep STN-DBS surgery led to a significantly wider TW than awake surgery for both DS and OS, with no difference in clinical effects between methods. 48) On the other hand, many reports have described DBS lead placement using only a neuroimaging guide, finding no difference in clinical effects from placement with MER guidance. 49 52) Although D-lead placement with only a neuroimaging guide has been reported 21) and the asleep STN-DBS surgery with D-lead is expected to increase in the future, no reports have examined indicators for lead placement or compared clinical effects.…”
Section: Introductionmentioning
confidence: 99%